Media Digital sebagai Sarana Edukasi: Peran Orang Tua Mengoptimalkan Konsumsi Konten Anak - Silalahi, Yetty Novel; Asbari, Masduki; Tambunan, Elsadai Rezeki Uli (Journal of Information Systems and Management (JISMA), 2025)
This study aims to examine the role of parents in optimizing the consumption of children's educational content in the digital age. The method used is a qualitative approach with listen and listen techniques, through the analysis of an interview between Gita Wirjawan and Anggia Kharisma (Chief Content Officer of Visinema Studio) which was published in a YouTube channel entitled "Pengobat Krisis Kontent Anak" (Gita Wirjawan, 2023). The Data was obtained by looking at the content of conversations to explore the views of content producers on the educational needs of children and their relevance to the role of parents in digital parenting. This study also explores the synergy between educational content and parenting can support optimal child development. Proper parenting allows children not only to enjoy entertainment from digital media, but also to acquire educational values that benefit their cognitive, social and emotional development. The results showed that the active involvement of parents in accompanying the consumption of digital media, contributes to the formation of children's character. With the right approach, digital media can serve not only as a means of entertainment, but also as an effective educational tool in shaping the character of a child from an early age.